PROGRAM PENGABDIAN MASYARAKAT USAHA MIKRO KECIL MENENGAH (UMKM) MENGENAI DESAIN KOMERSIALISASI DAN PROMOSI PRODUK MAKANAN INOVASI - Lutvi Azizah, Nuril Lutvi Azizah (Universitas Negeri Surabaya, 2020)
Mukti Adelia Jaya Trade Business is one of the innovation product trading business by utilizing bananatree waste such as dry leaves and banana cultivation. This business is located in Gading, PasuruanDistrict, East Java. In this modern era, innovation is needed to create new products in order to create newopportunities in society. Some promotional techniques have been done by partners, but until now thisTrade Business with its products still not widely known by the public. Therefore promotional techniquesshould be changed in accordance with the developments that occur in this society. In addition, the lack offunding or capital factors experienced by partners to be able to develop and promote its products. Themethod to be used is promotion of products over the internet, to enhance the promotion of innovationproducts as well as to provide designs for the commercialization of innovative product packaging. Internetbranding is offered to create a system consisting of websites that will connect with social media as amedium for sales and product promotion. The result of this community service program is that partners areable to build a brand digitally and able to publish innovation products with more commercial packaging tothe public, thus the production and sales process will increase.